2015
DOI: 10.1002/uog.14824
|View full text |Cite
|
Sign up to set email alerts
|

Fetal middle cerebral artery and umbilical artery pulsatility index: effects of maternal characteristics and medical history

Abstract: Objective To define the contribution of maternal variables which influence the measured fetal middle cerebral artery (MCA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 33 publications
2
23
3
Order By: Relevance
“…These include FHR which affects waveforms of the umbilical artery on a large scale. 23 In this study, however, differences found between AM and PM in and resting states in their study was smaller than ours (4.5 cm/s vs. Moreover, active healthy fetuses have increased MCA peak systolic velocity and decreased pulsatility index compared to those at rest.…”
Section: Discussioncontrasting
confidence: 74%
“…These include FHR which affects waveforms of the umbilical artery on a large scale. 23 In this study, however, differences found between AM and PM in and resting states in their study was smaller than ours (4.5 cm/s vs. Moreover, active healthy fetuses have increased MCA peak systolic velocity and decreased pulsatility index compared to those at rest.…”
Section: Discussioncontrasting
confidence: 74%
“…The measured values of UtA‐PI, UA‐PI, MCA‐PI, MAP, PlGF and sFlt‐1 were expressed as multiples of the median (MoM) after adjusting for variables from maternal characteristics and medical history that affect these measurements. Univariable and multivariable logistic regression analysis was used to determine if log 10 MoM of each biomarker had a significant contribution in predicting each adverse outcome.…”
Section: Methodsmentioning
confidence: 99%
“…The measured values of UtA‐PI, UA‐PI, MCA‐PI, MAP, PlGF and sFlt‐1 were expressed as multiples of the median (MoM) after adjustment for variables from maternal characteristics and medical history that affect these measurements. Univariable and multivariable logistic regression analyses were used to determine if log 10 MoM of each biomarker had a significant contribution in predicting each adverse outcome.…”
Section: Methodsmentioning
confidence: 99%